2016
DOI: 10.1155/2016/5059041
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Individual Participant Data for Exercise Meta-Analyses May Not Be Worth the Time and Effort

Abstract: Purpose. While individual participant data (IPD) meta-analyses are considered the gold standard for meta-analysis, the feasibility of obtaining IPD may be problematic. Methods. Using data from a previous meta-analysis of 29 studies on exercise in adults with arthritis and other rheumatic diseases, the percentage of studies in which useable IPD was provided was calculated. Results. Eight of 29 authors (28%, 95% CI = 11% to 44%) provided IPD. Using logistic regression, neither year of publication (odds ratio = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 56 An even more attractive approach to examine IIRD may be through the use of an individual participant data (IPD) meta-analysis, 57 although the retrieval of IPD may be challenging. 58 61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 An even more attractive approach to examine IIRD may be through the use of an individual participant data (IPD) meta-analysis, 57 although the retrieval of IPD may be challenging. 58 61 …”
Section: Discussionmentioning
confidence: 99%
“…56 An even more attractive approach to examine IIRD may be through the use of an individual participant data (IPD) meta-analysis, 57 although the retrieval of IPD may be challenging. [58][59][60][61] Third, to aid in conducting IIRD meta-analyses based on randomized controlled trials, it is suggested that original trial investigators report sample sizes as well as baseline, final, and change outcome means and standard deviations for both intervention and control groups. By doing so, this will help minimize potential bias as a result of excluding studies because of missing data.…”
Section: Overall Findingsmentioning
confidence: 99%
“…145 Consequently, the possibility exists that the findings observed at the group level in the current study would not be applicable at the individual level of the child or adolescent. While an individual participant data (IPD) metaanalysis would avoid this limitation, such an approach has to be considered with respect to (1) the inability to obtain IPD from original trial investigators, [146][147][148][149][150][151] (2) the loss of power and increased risk of bias with fewer eligible studies, (3) the substantially increased costs (up to 8 times greater) associated with conducting an IPD meta-analysis, 151,152 and (4) the general lack of differences in overall results observed between aggregate and IPD meta-analyses. [152][153][154][155][156][157] Finally, like any meta-analysis, the limitations of the included studies carry over to the current meta-analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Considered the 'gold standard' of meta-analyses, the potential advantages of an IPD meta-analysis, described in detail elsewhere (34) , include, but are not limited to, 'standardizing statistical analyses in each study; deriving desired summary results directly, independent of study reporting; checking modelling assumptions; and assessing participant-level effects, interactions and non-linear trends' (35) . However, one of the major disadvantages of an IPD meta-analysis is the ability to retrieve original data from study authors, with ranges of 25-100 % reported across different subject areas (36)(37)(38)(39) . As a result, this can lead to an increased risk of bias.…”
Section: Systematic Review With Meta-analysismentioning
confidence: 99%